Data Autodiscovery—The Role of the OPD - Adrian J. M. Cox; Andrew J. Milsted; Christopher J. Gutteridge (ISPRS International Journal of Geo-Information, 2016)
The importance of open data and the benefits it can offer have received recognition on the international stage with the signing of the G8 Open Data Charter in June 2013. The charter has an early focus on 14 high value areas, including transport and education, where governments have greater influence. In the UK, we have seen the funding of the Open Data Institute (ODI) with a remit to support small and medium sized enterprises (SMEs) in identifying benefits from using open data, whereas, within HE, open data discussion is in its infancy although is acknowledged as a sector challenge by the Russell Group of universities. There is an evident need for the academic community to influence the adoption of applications using linked open data techniques in data management and service delivery. This article introduces the concept of “data autodiscovery”, highlighting the role of the Organisation Profile Document (OPD) and its contribution to the early success of the UK National Equipment Portal, equipment.data, along with discussing the need for greater dialogue in linked and open data standards development.